2023
DOI: 10.3389/fpls.2023.1145670
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of flavonoids in strawberry fruits by FaMYB5/FaMYB10 dominated MYB-bHLH-WD40 ternary complexes

Abstract: Anthocyanins endowing strawberry fruit red color are regulated by the MYB-bHLH-WD40 complex. By analyzing the MYBs involved in the flavonoid biosynthesis in strawberry, we found that R2R3-FaMYB5 promoted the content of anthocyanin and proanthocyanidins in strawberry fruits. Yeast two-hybrid and BiFC assays confirmed that MBW complexes connected with flavonoid metabolism were FaMYB5/FaMYB10-FaEGL3 (bHLH)-FaLWD1/FaLWD1-like (WD40). Transient overexpression and qRT-PCR analysis revealed that disparate MBW models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
(78 reference statements)
2
10
0
Order By: Relevance
“…In apples, MdMYB90-like plays a key role in the regulation of anthocyanin biosynthesis [11]. In strawberry studies, yeast two-hybrid and BiFC assays also confirmed that the MBW complex can function in the flavonoid metabolic pathway in the form of FaMYB5/FaMYB10-FaEGL3 (bHLH)-FaLWD1/FaLWD1like (WD40) [12]. Similar findings were also presented in Arabidopsis thaliana and Norway spruce [13,14].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…In apples, MdMYB90-like plays a key role in the regulation of anthocyanin biosynthesis [11]. In strawberry studies, yeast two-hybrid and BiFC assays also confirmed that the MBW complex can function in the flavonoid metabolic pathway in the form of FaMYB5/FaMYB10-FaEGL3 (bHLH)-FaLWD1/FaLWD1like (WD40) [12]. Similar findings were also presented in Arabidopsis thaliana and Norway spruce [13,14].…”
Section: Introductionsupporting
confidence: 65%
“…In particular, the four families of genes, MYB, bHLH, AP2, and WRKY, were significantly positively correlated with some of the differential genes (PAL, C4H, F3 H, LDOX, DFR, CHI) and metabolites (Rutin, Trifolin, Luteolin, Quercetin, Catechin, and Anthocyanins). MYB and bHLH are two important transcriptional proteins in plants, and they have regulatory roles in anthocyanin biosynthesis in fruits such as apples [45,46], strawberries [12,47], and grapes [48,49]. They are usually involved in the regulation of color accumulation in plants through the MBW ternary complex with WD40 proteins [50].…”
Section: Discussionmentioning
confidence: 99%
“…MYB TFs typically do not function in isolation; instead, they often form complexes with other proteins (Xu et al, 2015; Nemesio-Gorriz et al, 2017). Among the various groups of TFs capable of interacting with MYB TFs, bHLHs have been identi ed (Yue et al, 2023). Within the DzbHLHs, DzbHLH1 has been recognized for its potential to bind with the previously reported DzMYB1, a crucial contributor to avonoid biosynthesis (Weerawanich et al, 2024).…”
Section: Y2h Assay Con Rmed the Interaction Between Dzmyb2 And Dzmyb3...mentioning
confidence: 99%
“…By increasing and inhibiting the activities of anthocyanin-related genes (MdF3H, MdDFR, and MdUFGT) and sugar-related genes (MdCWI1, MdVGT3, and MdTMT2), the MdMYB305-MdbHLH33-MdMYB10 complex balanced anthocyanin and sugar levels in red-fleshed apples [43,44]. FaMYB5 was also identified as an R2R3-MYB activator that is a component of the FaMYB5-FaEGL3-FaLWD1-like complex, which promotes anthocyanin and proanthocyanidin accumulation by directly targeting the F3'H and LAR promoters in strawberry [34,45].…”
Section: Introductionmentioning
confidence: 99%